Alteration of the co-substrate selectivity of deacetoxycephalosporin C synthase. The role of arginine 258. - Lee, H; Lloyd, MD; Clifton, I; Harlos, K; Dubus, A; Baldwin, J; Frere, J; Schofield, C (2001)
Deacetoxycephalosporin C synthase is an iron(II) 2-oxoglutaratedependent oxygenase that catalyzes the oxidative ring-expansion of penicillin N to deacetoxycephalosporin C. The wild-type enzyme is only able to efficiently utilize 2-oxoglutarate and 2-oxoadipate as a 2-oxoacid co-substrate. Mutation of arginine 258, the side chain of which forms an electrostatic interaction with the 5-carboxylate of the 2-oxoglutarate co-substrate, to a glutamine residue reduced activity to about 5% of the wild-type enzyme with 2-oxoglutarate. However, other aliphatic 2-oxoacids, which were not co-substrates for the wild-type enzyme, were utilized by the R258Q mutant. These 2-oxoacids "rescued" catalytic activity to the level observed for the wild-type enzyme as judged by penicillin N and G conversion. These co-substrates underwent oxidative decarboxylation as observed for 2-oxoglutarate in the normal reaction with the wild-type enzyme. Crystal structures of the iron(II)- 2-oxo-3-methylbutanoate (1.5 A), and iron(II)-2-oxo-4-methylpentanoate (1.6 A) enzyme complexes were obtained, which reveal the molecular basis for this "chemical co-substrate rescue" and help to rationalize the co-substrate selectivity of 2-oxoglutaratedependent oxygenases.